Kinaesthetic ability training improves unilateral neglect and functional outcome in patients with stroke: A randomized control trial - Sehim Kutlay; Aysun Genç; Haydar Gök; Derya Öztuna; Ayşe A. (Medical Journals Sweden, 2017)
Objective: To investigate the effects of kinaesthetic ability training with the Kinesthetic Ability Trainer (KAT) on unilateral neglect and functional outcomes in stroke patients. Study design: An assessor-blinded, randomized controlled, clinical trial. Methods: A total of 64 stroke patients with unilateral neglect (mean age 61 (standard deviation (SD) 12) years, 60.4% male, mean time since stroke 6.4 (SD 10.4) months, left hemiplegia 92.5%) were randomly assigned to a conventional rehabilitation programme (control group, n = 32) or KAT plus a conventional rehabilitation programme (KAT group, n = 32) for 4 weeks. Patients were assessed with the Behavioral Inattention Test (BIT) and Functional Independence Measure (FIM) before and after therapy. Results: Both groups showed significant improvements in all subscales of the BIT (conventional and behavioural) (p < 0.001) and the FIM motor scale (p < 0.001) after therapy. Recovery from neglect was assessed, based on the BIT cut-off scores. The recovery rate for behavioural BIT was 40% in the KAT group and 17.9% in the control group (p = 0.07), whereas recovery rates according to the conventional BIT were 16% and 10.7% in the KAT and control groups, respectively. Conclusion: Kinaesthetic ability training provides clinically meaningful improvement in stroke patients with unilateral neglect. It may be useful as an adjunctive therapy for rehabilitation in these patients.